FENOMENA TRANSPORT KOBALT-60 PADA LAPISAN TANAH - Ngasifudin . (BATAN, 2009)
The transport phenomena of cobalt-60 (Co-60) in the soillayer has been investigated using column and batch methods. The association of Co-60 with soil and its components were studied by extraction methods. The concentration profile of Co-60 in the soil column was composed of two logarithmic curves that showing Co-60 would be consist of mobile and immobile fraction. The immobile fraction of Co-60 was adsorbed by soil and was distributed near in the top of column. Although the mobile Co-60 was little sorbed by soil and migrated through the soil column, themaximum concentration of Co-60 in the effluents decreased slightly with increasing length of the soil column. Extraction of Co-60 from the soil and from its components showed that Co-60 was sorbed by manganese oxide and clay minerals. Manganese oxide is one of the soil components that could be decrease the maximum concentration of Co-60 in the effluents. Although the content of manganese oxide in the soil was 0.24-0.29%, manganese oxide is the important component to preventthe migration of Co-60 in the low acidic solution.Keywords : Transport phenomenon, Cobalt-60, soil component Telah dilakukan penelitian tentang fenomena gerakan Kobalt-60 (Co-60) pada lapisan tanah yang dilakukan secara kolom dan batch. Penggabungan Co-60.dengan tanah dan komponennya dipelajari dengan serangkaian teknik ekstraksi. Gambaran konsentrasi Co- 60 di dalam kolom tanah tersusun oleh dua kurva logaritma yang menunjukkan Co-60 terdiri atas fraksi gerak dan tidak-gerak. Fraksi Co-60 tidak-gerak diserap oleh tanah dan didistribusikan di dekat bagian atas kolom. Meskipun Co-60 fraksi gerak hanya sedikit terserap oleh tanah dan di-transportkan melalui kolom tanah, konsentrasi maksimum Co- 60 di dalam efluen sedikit menurun dengan kenaikan panjang kolom tanah. Ekstraksi Co-60 dari tanah dan komponennya menunjukkan bahwa Co-60 diserap oleh mangan dioksida dan komponen lempung. Mangan oksida merupakan salah satu komponen tanah yang dapat menurunkan konsentrasi maksimum Co-60 di dalam efluen. Bahkan kandungan mangan oksida 0,24-0,29% dalam tanah menjadi komponen penting untukmencegah proses transport Co-60 pada larutan keasaman rendah.Kata kunci : Fenomena transport, Kobalt-60, komponen tanah